Coastal reservoirs as a source of nitrous oxide: Spatio-temporal patterns and assessment strategy - Kam Tang (Science of The Total Environment, 2021)
Coastal reservoirs are widely used to solve the water scarcity problem in coastal cities. Because of anthropogenic wastes and alteration of hydroecological processes, these reservoirs may become hotspots for nitrous oxide (N2O) emissions. We measured the dissolved N2O concentrations and emissions at a high spatial resolution in a subtropical coastal reservoir in southeastern China, which was influenced by river runoff, aquacultural discharge, industrial discharge and municipal sewage. Both N2O concentration and emission showed large spatio-temporal variations correlated with nitrogen loading from the river and wastewater discharge. The mean N2O concentration and mission were significantly higher in the summer than in spring and autumn. Redundancy analysis showed that NH4-N explained the greatest variance in N2O emission, implying that nitrification was the main microbial pathway for N2O production. The mean N2O emission across the whole reservoir was 107 µg/m/h , which was more than an order of magnitude higher than that from global lakes and reservoirs. Based on Monte Carlo simulations, a minimum of 15 sampling points per km2 would be needed to produce representative and reliable N2O estimates in such a spatially heterogeneousaquatic system.